Depiction of women in selected Tshivenda poetry - Mareda, Vhutshilo (My University, 2023)
Women often receive characterisations of themselves in an idealised and stereotypical manner in literature, which warrants both contestation and the provision of remedial strategies against such representations of women in literature. Underpinned by African Feminism and the qualitative research approach, the study not only analysed a selection of Tshivenḓa poems, but also purposively analysed those poems that challenge the portrayal of women in a negative light by presenting them, arguably, as dignified human beings. Among the negative portrayals of women were depictions of women as slaves, catastrophic beings, subservient humans, sexual objects, and idiots, consequently culminating in the perception of women as marginalised in a variety of spheres. The study might contribute to the ongoing discourse on women liberation and empowerment.
Thesis (M.A.(African Language)) -- University of Limpopo, 2023
Keywords: Culture; Depiction; Feminism; Gender; Tshivenḓa; Poetry; Women; Women in literature; Venda poetry; Feminism -- Poetry